Multidisciplinary Management of Severe Hemorrhagic Stroke with Triple Challenge: Subarachnoid Hemorrhage, Intracerebral Hemorrhage, and Hydrocephalus-A Case Report - Wijaya, Andryadi; Jufan, Akhmad Yun (Faculty of Medicine, Brawijaya University, 2025)
Background: Hemorrhagic stroke, particularly subarachnoid hemorrhage (SAH) and intracerebral hemorrhage (ICH), is a neurological emergency associated with high morbidity and mortality, especially when complicated by increased intracranial pressure (ICP). This report aims to describe the comprehensive management of a patient with severe hemorrhagic stroke complicated by SAH, ICH, and hydrocephalus Case: This case report describes the management of a 69-year-old female with extensive SAH, ICH, ruptured anterior communicating artery aneurysm, and obstructive hydrocephalus. The patient presented with decreased consciousness post-seizure. Initial management included emergency external ventricular drain (EVD) placement and subsequent surgical clipping of the aneurysm. Non-invasive ICP monitoring using optic nerve sheath diameter (ONSD) demonstrated a reduction from 0.68 cm to 0.49 cm over seven days, reflecting successful ICP control. Complications included vasospasm managed with nimodipine, hypernatremia and polyuria suggestive of central diabetes insipidus treated with desmopressin, and nosocomial pneumonia due to serratia marcescens. Antibiotic therapy was escalated from ceftriaxone to meropenem and de-escalated to cefepime based on culture results. Despite optimal intensive care, the patient showed no significant neurological improvement (persistently low Glasgow Coma Scale [GCS]) and failed ventilator weaning. Given a poor prognosis (WFNS grade 4, Hunt & Hess grade 4, ICH score 3), the patient was transitioned to palliative care. Conclusion: This case highlights the importance of multidisciplinary management, non-invasive ICP monitoring, and timely transition to palliative care in severe hemorrhagic stroke.